HUMAN RIGHTS VIOLATIONS IN CYBERSPACE: INTERNET CENSORSHIP AND ONLINE SURVEILLANCE IN TURKEY - BURAK, Begüm (Cyberpolitik Journal, 2022)
Internet censorship has recently been a hotly-debated issue in Turkey. In the age of information society, online freedoms are seen as inseparable parts of liberal democracies. In contemporary world, not only in Turkey but in many other countries, there are many people who use social media platforms and digital news outlets as an alternative to traditional media that consist of TV channels, radio and print media. In such an environment, online freedoms are significant to be able to reach information. In addition, the right to have freedom of expression through online platforms such as social media sites has been an important aspect of individual liberties. This article is an attempt to address the restrictions exercised in the realm of online freedoms in Turkish context and to analyze how online censorship and online surveillance impact democracy. For this aim, some of the important internet censorship cases will be covered.